PENGARUH KEBIJAKAN INSTITUSI DAN PENGETAHUAN PENOLONG PERSALINAN TERHADAP PELAKSANAAN INISIASI MENYUSU DINI (IMD) DI PUSKESMAS KLATEN UTARA DAN RSUD KOTA SURAKARTA - ., Musta’in (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2012)
Background: Suckling not breastfeeding is a representation that early Breastfeeding is not a program of mother breastfeeding infant but infant that should actively find motherâs breast by him/herself. To make this program run smoothly, a policy should be made from the local institution. Objective: This research aims to study the effect of Institutional Policy and Delivery Assistantâs knowledge on the implementation of Early Breastfeeding in North Klaten Puskesmas (Public Health Center) and Surakarta City Local Hospital. Methods: This research employed a cross sectional study design. This study was taken place from March to August 2011. The population of research was all delivery assistants working in North Klaten Puskesmas (Public Health Center) and Surakarta City Local Hospital 59 person. Sample taken 40 delivery. 20 delivery from North Klaten Puskesmas (Public Health Center) (with Early Breastfeeding policy) and 20 delivery taken from Surakarta City Local Hospital (without Early Breastfeeding policy). The instrument used to collect the data was questionnaire. The data analysis was done using a multiple logistic regression model. Results: The researcher found that: (1) there is an effect of the Early Breastfeeding Policy existence in the institution on the implementation by the delivery assistants. The delivery assistants practicing in the institution with Early Breastfeeding Policy has probability nine times higher to conduct Early Breastfeeding than the one without Early Breastfeeding policy (p = 0.003), with strong significant category ( â¤ 0,01). (2) there is an effect of delivery assistantâs knowledge on the implementation of Early Breastfeeding in which the implementation of Early Breastfeeding is varied of 29% (Nagelkerke R2 = 29.10%). Conclusion: This research concludes that there is an effect of the Early Breastfeeding Policy existence in the institution on the implementation by the delivery assistants and there is an effect of delivery assistantâs knowledge on the implementation of Early Breastfeeding. Â Keywords: Early Breastfeeding, the effect of policy, institution policy, delivery assistant